CONTEXTUAL CLUES TECHNIQUE TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Mohammad Firdus (Widya Mandala Surabaya Catholic University, 2016)
This classroom action research is conducted to improve the students’ achievement on vocabulary through Contextual Clues Technique (CCT). The subject of the study is Class VIIIC students of SMPN I Labang Bangkalan in the academic year of 2013/2014. The class consists of 40 students. This study was conducted in three cycles and in each of the cycles is ended with one additional meeting for vocabulary teacher-made test. In this study, there were two types of data, the quantitative and qualitative data. The quantitative data were collected through pretest, test 1, test 2, and post test. The qualitative data were collected through observation checklist and field note, teacher’s diary, questionnaire, and interview. The quantitative data were analyzed using descriptive statistic to compare the mean scores of each test and also using T-test analysis to find the significance of the improvement. The qualitative data were analyzed using the descriptive analysis to know their improvement toward the use of CCT in learning vocabulary.